The Effect of Work Experience And OHS On Tax Office Staff's Performance - Agus Bandiyono; Renzo Ilham Ryandhi; Yuni Betti Mariani (Jurnal Manajemen, 2022)
This research aims to see the effect of work experience and occupational health and safety (OHS) on the staff's performance at the Tax Service Office (KPP). In this study, the research took place at KPP Madya Palembang and KPP Minyak dan Gas Bumi. The research method used is quantitative research. The population in this study were all staff at KPP Madya Palembang and KPP Minyak dan Gas Bumi totaling 70 people. Sampling using Slovin with a standard error of 10%. The data collection techniques used were interview and questionnaire techniques. The data were processed using multiple linear regression analysis models with the help of the SPSS program. From the research results, it is known that work experience and occupational safety and health have a positive and significant effect on the staff's performance of the tax service office.